Autologous Mesenchymal Stem Cell Transplantation for the Treatment of Chronic Heart Failure in Dilated Cardiomyopathy: A Clinical Case - Ivanova, Yulia V.; Gramatiuk, Svetlana M.; Estrin, Sergii I.; Kryvoruchko, Igor A.; Kravchenko, Tetiana V.; Peremot, Yakiv O.; Kovalchuk, Andrii O. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Dilated cardiomyopathy (DCMP) occupies a significant place among non-coronary heart diseases leading to chronic heart failure (CHF). Due to the high mortality rate associated with DCMP, there is a continuous search for alternative heart-preserving treatment methods as “bridges” to heart transplantation. One of the promising approaches is stem cell therapy. Aim. To describe our own successful case of intravenous transplantation of autologous mesenchymal stem cells (MSCs) as a palliative treatment for CHF associated with DCMP. Clinica case. A 48-year-old man with DCMP underwent specialized medical treatment for CHF (stage C) in the cardiology department of the Kharkiv Regional Cardiology Centre. The treatment was supplemented by a double intravenous administration of autologous MSCs, with a one-month interval between the two procedures. The first injection, performed against the background of acute left ventricular failure (ALVF), contained 6 million MSCs, while the second administration involved 4 million MSCs. To assess the patient’s clinical status and heart function, physical examination, electrocardiography, and echocardiography were performed at the time of each injection and one month after each procedure. No adverse reactions or side effects were observed following either procedure. Discussion. Instrumental evaluation demonstrated that the double intravenous administration of MSCs led to a gradual improvement in overall left ventricular contractility, a progressive reduction in both systolic and diastolic left ventricular volumes, a decrease in left atrial volume, and regression of mitral regurgitation severity from grade II to grade I. Additionally, it contributed to the complete elimination of persistent ventricular extrasystole. These functional improvements alleviated CHF symptoms (from stage C to stage B), prevented further episodes of ALVF, reduced the need for diuretics, and increased the patient’s tolerance to physical exertion. Positive dynamics in the patient’s clinical condition and echocardiographic parameters were observed as early as one month after each MSC administration. Conclusions. The intravenous administration of autologous MSCs improves the systolic function of the affected heart muscle and can be considered a promising palliative therapy as part of the comprehensive treatment of CHF associated with DCMP. However, the methodology of its clinical application requires further investigation.